Evaluation of syllabus for sport injuries and rehabilitation in the teaching guide-book for primary and intermediate schools in Iraq - Jaber, Mona (Journal of Physical Education, 2015)
Due to competition elements in the physical education lesson and playing sports (using sport tools and playing instruments), pupils/students are facing several injuries. Sport injuries regard as a negative sign for the development of sport in school. This can cause prominent damage in the human tissues (muscular tissue, skeleton, etc), and as a result these injuries may be resulted in a long term physiological, chemical and psychological effects of pupil/student. Surprisingly, the teaching guide-book for primary and intermediate schools has not included neither the common injuries may occur in the physical education lesson or their first aid treatment that teacher can handle in the playground of school before sending injured pupil/student to hospital. As a matter of fact, curing period for injured human organism during sport lesson is depending on how injured pupil/student received first aid treatment on playing site by physical education teacher. The aim of this study is to evaluate the syllabus for sport injuries and their rehabilitation in the teaching guide-book for physical education subject provided by Directorate of Syllabus/ Iraqi Ministry of Education. This work has concluded that: 1. Syllabus for sport injuries in teaching guide-book for physical education subject is dealt with general injuries that could happen without practicing sport. Further, it has not covered injuries may occur upon practicing approved type of sport, for individual or a team, mentioned in the syllabus. 2. First aid and treatment approach mentioned in the syllabus is designed to be given in the surgery, rather than to be handled in the school by physical education teacher. It is well know that first aid on site is the crucial factor in curing period of injury. Finally, the researcher recommended including the common deformation of skeleton and their treatment in the physical education syllabus for the primary and intermediate schools